(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
One of the most common requirements in modern industrial applications is to minimize the costs associated with the operation, maintenance and possible repairs of the component systems. In industrial processes, induction motors are the most commonly used electromechanical converters in electrical drive systems. The extensive development of power electronics, as well as the relatively low manufacturing cost of asynchronous motors has determined a very high incidence of the presence of induction motor drive systems in industrial systems. The use of semiconductor devices to control the drive parameters of induction motors facilitates the tuning of the system and thus greatly improves its flexibility. However, the optimal use of such electric motors is limited due to the possibility of specific defects caused by the quality of the power supply. In this context, this paper proposes an analysis of the defects that frequently appear in the case of induction motors in industrial electrical drive systems as a result of deviations from the quality of the electrical energy of their power system parameters. Two deviations from the power quality are mainly investigated, namely, the imbalance of the voltage value applied to the motor phases, respectively the harmonic distortions of the waveforms of the voltages applied to the motor. At the same time, an analysis of the failure rate is made according to various characteristics of the induction motors.